YIELD STABILITY OF NEW HYBRID RICE ACROSS LOCATIONS - Satoto, Satoto; Rumanti, Indrastuti Apri; Widyastuti, Yuni (AGRIVITA, Journal of Agricultural Science, 2016)
The adaptation of hybrid rice varieties mostly are in specific location and season, but there are some of the varieties have a wide adaptation then adopted by the farmer in the large area. Replicated yield trials were conducted to study the stability of hybrid rice yield and identify the best location to optimize their yield per ha. We have conducted the trials in three location such as Sukamandi, Salatiga and Malang during two seasons in 2011. We are analyzing data across location and season  using AMMI and Eberhart Russel methods. The AMMI analysis showed that the  IR79156A/PK88 was adaptable to favorable environments but unstable. This hybrid is always performing well and produce the higher yield compare to check variety. Some of other hybrids  were good only in specific location, i.e. IR62829A/BP2280-1E-12-22 and IR58029A/BP2 280-1E-12-22. Those hybrids produced higher yield in Salatiga and Malang, respectively. Seem to AMMI analysis, the result of Eberhart and Russells method also showed that IR79156A/PK81  was the best hybrid with regression slope (b) around 1 with the yield average higher than average of all hybrids. It indicated that this hybrid has a wide adaptation and probably can be cultivated in the wider ecosystem.